1976
DOI: 10.1111/j.1365-2621.1976.tb01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic Lipid Peroxidation in Microsomes of Chicken Skeletal Muscle

Abstract: An enzymic system for the oxidation of microsomal lipids in the presence of Fe+S, ADP and NADPH or NADH has been demonstrated in the microsomai (sarcoplasmic reticular) fraction of chicken skeletal muscle. Heat, deoxycholate, chelating agents and butylated hydroxyanisole inhibited the oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…However, several studies have indicated that in raw meat lipid peroxidation could develop during storage time induced by enzymatic (Lin and Hultin 1976;Asghar et al, 1988) and inorganic iron activity (Kanner et al, 1988a). Because unsaturated fatty acids are susceptible to undergo lipid oxidation (Dahle et al, 1962), it is likely that their enrichment in the meat lipid composition may result in higher susceptibility to lipid oxidation, particularly when the meat is under prolonged storage and commercial display.…”
Section: Introductionmentioning
confidence: 96%
“…However, several studies have indicated that in raw meat lipid peroxidation could develop during storage time induced by enzymatic (Lin and Hultin 1976;Asghar et al, 1988) and inorganic iron activity (Kanner et al, 1988a). Because unsaturated fatty acids are susceptible to undergo lipid oxidation (Dahle et al, 1962), it is likely that their enrichment in the meat lipid composition may result in higher susceptibility to lipid oxidation, particularly when the meat is under prolonged storage and commercial display.…”
Section: Introductionmentioning
confidence: 96%
“…The iron‐catalyzed lipid oxidation system in liver or muscle microsomes using NADPH as the reducing agent has been reported in terrestrial species such as rats, chickens and beef cattle (Hochstein and Ernster 1963; Lin and Hultin 1976; Rhee et al. 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The lipid oxidation in subcellular fractions reported by various investigators is mediated by Fe2+ iron maintained enzymatically in the reduced form by NADPH. Hultin and his associates (Lin and Hultin, 1976;Player and Hultin, 1977) showed that chicken breast or leg muscle micro somes produced malonaldehyde when incubated with appropriate components (NADH or NADPH, ADP and iron) of an oxidation system. Similar lipid oxidation systems associated with beef and pork muscle micro somes were reported by Rhee et al (1984) and Rhee and Ziprin (1987), respectively.…”
Section: Enzymatic Lipid Oxidationmentioning
confidence: 99%